The Tora Tigga Ultramafic Complex, southern Dir district - Jan, M. Qasim; Banaras, Muhammad; Ghani, Abdul; Asif, Muhammad (Journal of Himalayan Earth Sciences, 1983)
The ultramafic rocks of Tora Tigga near Munda are emplaced in amphibolites of the Kohistan tectonic zone along the Main Mantle Thrust. The amphibolites are represented by metamorphosed gabbros and lo rites of the Chilas layered complex, and garnet-bearing mafic to intermediate plutons. The ultramafites include dunites and a variety of peridotites, pyroxenites, and hornblendite. The hornblendites are the most abundant of these, are coarse-grained to pegmatite, and contain deformed felsic dykes and veins. The origin of the olivine- and pyroxene ulltramafites is not clear; they might be alpine-type or, more probably, cumulates of the Chilas complex and related to the metamorphosed gabbros and norites. Field relations and textural features suggest that the hornblendites have formed by metasomatism of the various rocks in the area.